2017
DOI: 10.1073/pnas.1706801115
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical thyroid hormone signaling mediates cardiometabolic effects in vivo

Abstract: Thyroid hormone (TH) and TH receptors (TRs) α and β act by binding to TH response elements (TREs) in regulatory regions of target genes. This nuclear signaling is established as the canonical or type 1 pathway for TH action. Nevertheless, TRs also rapidly activate intracellular second-messenger signaling pathways independently of gene expression (noncanonical or type 3 TR signaling). To test the physiological relevance of noncanonical TR signaling, we generated knockin mice with a mutation in the TR DNA-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 53 publications
2
113
1
1
Order By: Relevance
“…Deiodinases type 1and 2 (D1 and D2) activate THs whereas D3 carries out inactivation of T4 and T3 (34). Lastly, THs can either positively or negatively regulate gene transcription via the thyroid hormone receptor (THR) by binding to thyroid hormone response elements (TREs) located on the promotors of target genes or even via direct modulation of gene expression (35). THRs are encoded by the thyroid hormone receptor α (THRA) and thyroid hormone receptor β (THRB) genes each with specific transcriptional responses (36,37).…”
Section: Overview Of the Hypothalamus-pituitary-thyroid Axismentioning
confidence: 99%
“…Deiodinases type 1and 2 (D1 and D2) activate THs whereas D3 carries out inactivation of T4 and T3 (34). Lastly, THs can either positively or negatively regulate gene transcription via the thyroid hormone receptor (THR) by binding to thyroid hormone response elements (TREs) located on the promotors of target genes or even via direct modulation of gene expression (35). THRs are encoded by the thyroid hormone receptor α (THRA) and thyroid hormone receptor β (THRB) genes each with specific transcriptional responses (36,37).…”
Section: Overview Of the Hypothalamus-pituitary-thyroid Axismentioning
confidence: 99%
“…To study the biological relevance of non-genomic actions in a longer time frame, different animal models were made recently, providing some interesting genetic support for non-genomic actions in vivo (Martin et al 2014, Hönes et al 2017. However, it needs to be kept in mind that mutations in the DNA-binding domain of TRs can also produce unexpected gain-of-function effects, that is binding to DNA motifs that are not bound by a wildtype receptor.…”
Section: Non-genomic Vs Genomic Effectsmentioning
confidence: 99%
“…The precise mechanisms often depend on the cellular system, as some have reported that 3,3′,5-triiodothyronine (T3) activates the PI3 kinase pathway through cytosolic TRβ (Cao et al 2005), while others showed an action of T3 on a plasma membrane-bound TRα, which in turn activates the ERK pathway (Kalyanaraman et al 2014). There is also some support for the relevance of these non-genomic pathways in vivo, indicating an involvement of cytosolic TRβ and PI3 kinase signalling in mouse hippocampal synpase maturation (Martin et al 2014) or non-genomic TRα1 action in the regulation of cardiac functions (Hönes et al 2017). However, the individual contributions of genomic and non-genomic effects for specific well-known effects of TH often remain enigmatic, and cannot be generalized for all cellular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Der formale Beweis für diese schnelle, sog. nicht kanonische TH-Wirkung im Organismus gelang erstmals im SPP1629 über spezifische Mausmodelle, in denen mutierte TR-Isoformen exprimiert sind, die mit den TH-responsiven Elementen (TRE) im Zellkern nicht mehr interagieren können, aber dennoch TH-abhängige, physiologische Wirkungen entfalten [55]. Die hierbei identifizierten nicht kanonischen Wirkungen von TH betreffen den Energiestoffwechsel, den Triglyzerid-Metabolismus und den Herzrhythmus.…”
Section: Kanonische Und Nicht Kanonische Th-wirkungunclassified